(untitled) (Research, Society and Development, 2024)
In this paper, a proposal is presented for using the Arduino platform in the teaching/learning process of fundamentals of electricity in Physics. Physics teaching has faced difficulties, which can sometimes be structural or even cultural. The difficulty comes structurally from the way the teaching of this subject was designed and also due to the lack of structure. And the cultural difficulty comes from the rigid way of teaching Physics, where the teacher is always the holder of all knowledge and the students only mechanize the process through reproduction. In this sense, the active methodology presents itself as a possibility for a paradigm shift, where the student becomes the protagonist and active participant, bringing several benefits. Therefore, the proposal of this work is to carry out the application of classes with active methodology with the help of the Arduino board to teach Physics to high school students, and subsequently carry out an evaluation with qualitative/quantitative research. The results obtained are superior, and it is noteworthy that 99% of students recommend more classes as in Physics subjects, and 100% of students evaluated the active methodology as having good potential in relation to the traditional methodology.